Application of optical orbital angular momentum to rotation measurements - Luyi Wang; Jiantao Ma; Min Xiao; Yong Zhang (Results in Optics, 2021)
In recent years, the orbital angular momentum (OAM) of light with a central phase singularity composed of a specific topological charge has attracted increasing attentions. In addition to the wide range of applications of OAM in optical manipulations and optical communications, the special angular spatial structure of OAM offers irreplaceable advantages for use in rotation measurement. Because of the relationship between OAM and angular position, the azimuthal information of optical fields can be acquired via detection of OAM. Several techniques based on this concept have been proposed to sense objects remotely using their angular motion. This article introduces the applications of OAM in object orientation recognition, rotation sensing, small angle measurement and rotating object imaging.